Balancing Innovation and Efficiency: The Role of Ambidextrous Leadership and Person-Job Fit in Enhancing Auditor Performance through Innovative Work Behavior - Nababan, Boy Chandra; Lumbanraja, Prihatin; Siahaan, Elisabet (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to examine the influence of ambidextrous leadership and person-job fit on auditor performance, mediated by innovative work behavior. A quantitative approach was applied by distributing a structured questionnaire to 125 Functional Auditors. Descriptive statistics and path analysis were used to examine direct and indirect effects of Ambidextrous Leadership and Person-Job Fit on performance, mediated by Innovative Work Behavior. Data analyzed to test seven hypotheses, ensuring robust statistical validation. Results confirm that Ambidextrous Leadership and Person-Job Fit significantly enhance Employee Performance through Innovative Work Behavior. Leadership leans toward exploitation over exploration, limiting innovation, while job fit is strong in technical competencies but weaker in personality alignment. Innovative Work Behavior mediates the relationships, boosting performance by fostering creative problem-solving.